Reconstruction of the lower lip using bilateral commissurotomy and advancement of skin, muscle, and mucosal flaps. Issue 9 (November 2016) - Sayan, A.; Paraneetharan, S.; Hsu, D.W.K.; Ilankovan, V.
Abstract: Reconstruction of a composite defect of the lower lip after oncological resection is challenging, and it is essential to consider both functional and aesthetic components when repairing lips. We report a technique that can be used to repair anything ranging from 30% to the whole of the lower lip with a bilateral commissurotomy and advancement of skin, muscle, and mucosal flaps. This technique helps to achieve good oral function, excellent lip function, and a pleasant aesthetic appearance. It also prevents microstomia and allows patients to maintain normal sensory innervation.